The Laws of London? IV Æthelred in Context. - Naismith, Rory (London Journal, 2019)
The law-code known as 'IV Æthelred' has been identified since the mid-nineteenth century as a text concerned with tolls, trading and currency in London, dated to around the year 1000. This contribution argues that 'IV Æthelred' may have had little if anything to do with Æthelred II (978-1016). By re-evaluating the law-code's transmission, contents and date, it is proposed that the text consists of two distinct segments, probably put together around 1100 and surviving only in Latin translation. One part is a series of tenth-century decrees on currency crimes, and represents the most detailed statement on this topic to survive from Anglo-Saxon England. The other relates more specifically to London, laying out the tolls incurred by merchants coming to the city from across northern Europe. Frequent use of French terminology marks this portion of the text out, and suggests a date in the aftermath of the Norman Conquest.